Diagnostic distribution and pitfalls of glandular abnormalities in cervical cytology: a 25-year single-center study - Jung-A Sung; Ilias P. Nikas; Haeryoung Kim; Han Suk Ryu; Cheol Lee (Korean Society of Pathologists & the Korean Society for Cytopathology, 2022)
Background Detection of glandular abnormalities in Papanicolaou (Pap) tests is challenging. This study aimed to review our institute's experience interpreting such abnormalities, assess cytohistologic concordance, and identify cytomorphologic features associated with malignancy in follow-up histology. Methods Patients with cytologically-detected glandular lesions identified in our pathology records from 1995 to 2020 were included in this study. Results Of the 683,197 Pap tests performed, 985 (0.144%) exhibited glandular abnormalities, 657 of which had tissue follow-up available. One hundred eighty-eight cases were cytologically interpreted as adenocarcinoma and histologically diagnosed as malignant tumors of various origins. There were 213 cases reported as atypical glandular cells (AGC) and nine cases as adenocarcinoma in cytology, yet they were found to be benign in follow-up histology. In addition, 48 cases diagnosed with AGC and six with adenocarcinoma cytology were found to have cervical squamous lesions in follow-up histology, including four squamous cell carcinomas. Among the cytomorphological features examined, nuclear membrane irregularity, three-dimensional clusters, single-cell pattern, and presence of mitoses were associated with malignant histology in follow-up. Conclusions This study showed our institute's experience detecting glandular abnormalities in cervical cytology over a 25-year period, revealing the difficulty of this task. Nonetheless, the present study indicates that several cytological findings such as membrane irregularity, three-dimensional clusters, single-cell pattern, and evidence of proliferation could help distinguishing malignancy from a benign lesion.